Words and Acts in the History of Latin American Constitutionalism - Aguero, Alejandro (2018)
This critical essay, offers an analysis of the recent book by José María Portillo titled Historia Mínima del Constitucionalismo en América Latina. The book is an occasion to reflect on the new approaches on Spanish constitutionalism and to put forward some questions about recurrent problems on Latin American constitutional culture.